Characteristics of initial public offerings on Kuala Lumpur stock exchange - Chua, Khoon Hua (2014)
This project examines the time variation of risk Malaysian Initial Public Offerings (IPOs). It also tests the correlation between underpricing of IPOs on Kuala Lumpur Stock Exchange (KLSE) with the risk level of the share issues, the subscription rate, the gross proceeds of the issue and the firm’s market value. Brief background information of KLSE and its recent performance as an emerging market is also provided.